Orta Doğu’da küreselleşme ve kimlik ekseninde müzecilik : Katar İslam Sanatları Müzesi ve Modern Arap Sanatları Müzesi örnekleri - Doğan, Oytun (My University, 2022)
Araştırma, Orta Doğu toplum yaşantısının bilgi iktidar ilişkilerinin işleyişinde müzenin yerini anlamak üzerine olmuştur. Müzenin sadece bina ve içindeki eserler ile değerlendirilmesi değil ayrıca içinde bulunduğu toplum için ne anlam ifade ettiği üzerine bir inceleme olmuştur. Bu çerçevede süreç, kimlik ve küresel açıdan anlaşılmaya çalışılmıştır. Kimlik incelemesi müzenin uluslaşma aşamasında her ülkenin başvurduğu önemli bir referans noktası olarak seçiminin incelenmesi üzerinedir. Bu amaçla müze içine giren nesnenin sahiplik ilişkisi ve maddi bir yer işgal eden kurumun yönelimi incelenmiştir. Güncelin anlaşılmasında bu yönelim müzenin bir kimlik inşa eden kurum olarak gelişimine karşılık gelmiştir. İkinci adımda ise küreselleşme fikrinin oluşumu ve müzenin bilgi iktidar aygıtı olarak kullanımı ele alınmıştır. Müzenin kurum olarak oluşumun batılı bir düşünce olması ve kolonyal etki ile dünya geneline yayılması başlangıç noktasını oluşturmuştur. Emperyalist yayılmacılık ile birlikte müze kurumunun ilhak topraklarında görülmesi ve kültürel ilhakın da bu sayede sağlanması gerçekleşmiştir. Bu açıdan başlayan bilgi inşası süreç içinde yerellik bağlamında bir işlev göstermiş ve eskinin emperyalist ülkelerinin toprak üzerine hak iddia etme yönelimini dönüşüme uğratarak yerellik bağlamında bir bilgi inşa aracı olarak kullanılmıştır. Bu açıdan yerel iktidarlar tarafından inşa edilen sürecin toplumsal karşılığı ve yerellik bağlamında toplum için ifade ettiği anlam ilişkileri incelenmiştir. Bu amaçla müze içinde yer alan nesnelerin ifade ettiği anlam ve bu anlam ilişkilerinin yerellik bağlamında algısı anlaşılmaya çalışılmıştır. Müzenin modern devletlerin merkezi bir kültür enstitüsü olarak görünümü ve Orta Doğu toplum incelenmesinde gelenek ve modernlik arasındaki ilişkide aldığı rol incelenmiştir. Bu açıdan müze incelenme süreci tekil olarak Orta Doğu’ya bağlı olarak değil Batılı örneklerin de incelenmesi üzerine olmuştur. Bu süreç sonucunda başlangıcı emperyalist bilgi iktidar aracı olarak gelişen kurumun yerel bağlamda kabulü ve toplum için algısının gerilim taşıyıp taşımadığı anlaşılmaya çalışılmıştır. Bu açıdan araştırmada Katar’ın İslam Sanatları ve Modern Sanatlar Müzeleri örneklem alınarak inceleme yapılmıştır. Topluluk ve müze ilişkisinin boyutları bu sayede ortaya çıkarılmıştır.

The research is based on understanding the place of the museum in the functioning of knowledge power relations of Middle Eastern life. The museum has not only been evaluated with the building and the works in it, but also has been taken as a mechanism to an examine its meanings for the society in which it is located. This was sought to understand in terms of identity and globalism. Identity analysis is about the selection of the museum as an important reference point applied by each country during the nationalization processes. For this purpose, the ownership relationship of the object entering the museum and the orientation of the institution occupying a material place were examined. This orientation in understanding the contemporary corresponded to the development of the museum as an identity-building institution. In the second step, the formation of the idea of globalization and the use of the museum as an information power device are discussed. The establishment of the museum as an institution was a western idea and the spreading of the museum around the world with the colonial effect formed the starting point. With the imperialist expansionism, the museum institution was seen in the annexed territory and the cultural annexation was ensured in this way. The knowledge building that started in this respect has functioned in the context of locality and has been used as a knowledge building tool there by transforming the former imperialist countries' tendency to claim land. In this respect, the social equivalent of the process built by local governments and the meaning relations it expresses for the society in the context of locality have been examined. For this purpose, the meaning of the objects in the museum and the perception of these meaning relations in the context of locality were tried to be understood. The view of the museum as a central cultural institute of modern states and its role in the relationship between tradition and modernity in the study of Middle Eastern society are examined. From this point of view, the process of examining the museum was not based on the Middle East alone, but on the examination of western examples as well. As a result of this process, it has been tried to understand whether the institution, which started as an imperialist information power tool, is accepted in the local context and whether its perception for the society carries tension. In this respect, the research will be examined by taking the Islamic Arts and Modern Arts Museums of Qatar as a sample. In this way, the dimensions of the relationship between the community and the museum will be revealed.
Keywords: alone; an examine its meanings for the society in which it is located; and the meaning relations it expresses for the society in the context of locality have been; and the orientation of the institution occupying a material place were examined; Antropoloji; Art museums, Islamic; As a result of this process; been tried to understand whether the institution; between the community and the museum will be revealed; between tradition and modernity in the study of Middle Eastern society are examined; but also has been taken as a mechanism to; but on the examination of western examples as well; claim land; evaluated with the building and the works in it; examined; For this purpose; From; globalization and the use of the museum as an information power device are discussed; Identity analysis is about the selection of the; In the second step; In this respect; In this way; is accepted in the local context and whether its perception for the society carries; it has; Katar; Katar The research is based on understanding the place of the museum in the functioning; knowledge building tool there by transforming the former imperialist countries' tendency to; Kültürel Çalışmalar; Middle East; Modern Arts Museums of Qatar as a sample; museum as an identity-building institution; museum as an important reference point applied by each country during the nationalization; Museums; Müzecilik; Müzeler; of knowledge power relations of Middle Eastern life; orientation in understanding the contemporary corresponded to the development of the; Orta Doğu; point; power tool; processes; Qatar; Sanat müzeleri, İslam; Sanat Tarihi; Social conditions; Sosyal durum; Sosyoloji; spreading of the museum around the world with the colonial effect formed the starting; started in this respect has functioned in the context of locality and has been used as a; tension; territory and the cultural annexation was ensured in this way; the dimensions of the relationship; The establishment of the museum as an institution was a western idea and the; the formation of the idea of; The knowledge building that; the meaning of the objects in the museum and the perception of; the museum as a central cultural institute of modern states and its role in the relationship; The museum has not only been; the museum institution was seen in the annexed; the ownership relationship of the object entering the museum; the process of examining the museum was not based on the Middle East; the research will be examined by taking the Islamic Arts and; the social equivalent of the process built by local governments; The view of; these meaning relations in the context of locality were tried to be understood; This; this point of view; This was sought to; understand in terms of identity and globalism; which started as an imperialist information; With the imperialist expansionism